Orthostatic Hypotension and Antiparkinsonian Drugs: A Systematic Review and Meta-analysis. (September 2022) - Nimmons, Danielle; Bhanu, Cini; Orlu, Mine; Schrag, Anette; Walters, Kate
Background: Orthostatic hypotension (OH) is multifactorial in Parkinson's disease (PD). Antiparkinsonian medication can contribute to OH, leading to increased risk of falls, weakness and fatigue. Methods: We conducted a systematic review and meta-analysis of randomised controlled trials (RCTs) of antiparkinsonian drugs associated with OH as an adverse effect, compared to placebo. We searched EMBASE, MEDLINE and Web of Science databases until November 2020. Analysis used fixed-effects models and the GRADE tool to rate quality of evidence. Meta-analysis was performed if 3 or more studies of a drug group were available. Results: Twenty-one RCTs including 3783 patients were included comparing 6 PD drug groups to placebo (MAO-B inhibitors, dopamine agonists, levodopa, COMT inhibitors, levodopa and adenosine receptor antagonists). OH was recorded as an adverse event or measurement of vital signs, without further specification on how this was defined or operationalised. Meta-analysis was performed for MAO-B inhibitors and dopamine agonists, as there were 3 or more studies for these drug groups. In this analysis, compared with placebo, neither MAO-B inhibitors or dopamine agonists were associated with increased risk of OH, (OR 2.28 [95% CI:0.81–6.46]), (OR 1.39 [95% CI:0.97–1.98]). Conclusions: Most studies did not specifically report OH, or reporting of OH was limited, including how and when it was measured. Furthermore, studies specifically reporting OH included participants that were younger than typical PD populations without multimorbidity. Future trials should address this, for example, , by including individuals over the age of 75, to improve estimations of how antiparkinsonian medications affect risk of OH.